PENGEMBANGAN PERANGKAT PEMBELAJARAN INKUIRI TERBIMBING BERBASIS AKTIVITAS HIGHER ORDER THINKING PADA KELAS V SEKOLAH DASAR - Widiarta, I Dewa Gede Putra; Parmiti, Desak Putu; Margunayasa, I Gede (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2019)
This study aims to develop a guided inquiry learning tool based on higher order thinking (HOT) activities on the theme of 9th subtheme 1 grade V elementary school.This research is a development research conducted using the ADDIE model with stages, namely (1) analyze, (2) design, (3) development, (4) implementation, and ( 5) evaluation. However, the implementation phase and the evaluation stage were not carried out due to time constraints. The subject of this research is the learning kit consisting of syllabus, lesson plans, and LKPD. The instrument used to measure the validity of the device is the learning device assessment sheet to the expert. The device validation data that has been collected is then analyzed using the mean formula to find out the average score of device validity. The results of data analysis show that: (1) the average syllabus validation score is 4.73, is in very good qualifications, the average RPP validation score is 4.75, is in a very good qualification, the average LKPD validation score is 4.86, are in very good qualifications, and (2) the acquisition of the results of the validity of the equipment (syllabus, RPP, and LKPD) shows that the equipment that has been developed has very good qualifications.